What drives potential accessibility decomposition? Temporal and spatial variability of the impact of infrastructure and population components in France, Spain, and Poland in the years 1960–2020 - Piotr Rosik; Marcin Mazur; Marcin Stępniak; Tomasz Komornicki; Sławomir Goliszek; Patryk Duma; Paweł Churski (Journal of Transport and Land Use)
Changes in potential accessibility are the effect of both the expansion of transport infrastructure and shortening travel times, as well as land-use processes, e.g., changes in population size and distribution. The aim of the paper is to indicate the spatial and temporal variability of the impact of the infrastructure and population components on changes in potential accessibility in France, Spain and Poland over six decades in the period 1960-2020. The simulations for various parameters of the impedance function presented indicate that in nationwide conditions the greatest improvement in accessibility as a result of the infrastructure component takes place at a specific value of the so-called half-life, predominantly about 60 minutes. For the population component, the length of the trip is less important in assessing changes in accessibility. It has been shown that periods of very high impact of the development of road infrastructure on improving accessibility are mostly limited to a single decade in each of the countries examined, i.e., in the 1970s in France, the 1990s in Spain and the 2010s in Poland. Three approaches to distinguishing typologies have been proposed depending on the use of three dimensions of the interplay of the impact of accessibility components on changes in accessibility. These three dimensions are: (1) the dominance (of strength) of the components, (2) the combination of influence signs of the components and (3) the ratio of the components.